The Effect of the VAKVID E-Booklet (Electronic Booklet of the Covid-19 Vaccine) on Knowledge and Attitude of Understanding the Covid-19 Vaccine - Meutia Zuhra; Inong Sri Rahayu; Aulia Rahmi (Majalah Kesehatan Indonesia, 2022)
There are many pros and cons to the government's policy regarding the Covid-19 Vaccine for students in schools. Low knowledge and understanding of the Covid-19 vaccine are one of the causes. Socialization and education related to the Covid-19 Vaccine are one of the efforts to support this vaccination program. The purpose of this study is to determine the influence of education using the E-Booklet VAKVID (Electronic Covid-19 Vaccine Booklet) on knowledge and attitudes of Understanding the Covid-19 Vaccine. Pre-Experimental Research with the design of One group pretest-posttest used a purposive sampling technique in sampling as many as 230 students of Madrasah Tsanawiyah (Junior Hogh School) Lhokseumawe City, knowledge and attitudes of understanding the Covid-19 vaccine were measured using questionnaires, analyzed through statistical tests Shapiro Wilk continued with the Wilcoxon test. The data from the study showed that there were differences in knowledge and attitudes of understanding the COVID-19 vaccine before and after education using the VAKVID e-Booklet. The average knowledge pretest score is 5.34±1.398 and the post-test score is 6.93±0.960, while the Attitude pretest score is 15.00±1.884 and the post-test score is 16.33±0.923. The influence of education using the VAKVID E-Booklet method provides a significant difference in knowledge (p = 0.000) and attitudes (p = 0.000) regarding Understanding the Covid-19 Vaccine. Education using the e-Booklet VAKVID method can increase knowledge and attitudes of understanding the Covid-19 vaccine in students. Abstrak: anyak pro dan kontra terhadap kebijakan pemerintah terkait Vaksin Covid-19 untuk siswa di sekolah. Pengetahuan dan sikap pemahaman vaksin Covid-19 yang rendah merupakan salah satu penyebabnya. Sosialisasi dan edukasi terkait Vaksin Covid -19 merupakan salah satu upaya dalam mendukung program vaksinasi ini . Tujuan penelitian ini untuk mengetahui pengaruh edukasi  menggunakan metode E-Booklet VAKVID (Elektronik Booklet Vaksin Covid-19) terhadap pengetahuan dan sikap Pemahaman Vaksin Covid-19. Penelitian Pre Eksperimental dengan desain One group pretest-posttest ini menggunakan teknik purposive sampling dalam pengambilan sample sebanyak 230 siswa Madrasah Tsanawiyah Kota Lhokseumawe, pengetahuan dan sikap pemahaman vaksin Covid-19 diukur menggunakan kuesioner, dianalisis melalui uji statistik Shapiro Wilk dilanjutkan uji Wilcoxon.Data hasil penelitian menunjukkan terjadi perbedaan pengetahuan dan sikap pemahaman vaksin Covid-19 sebelum dan sesudah edukasi menggunakan metode e-Booklet VAKVID. Rerata skor pretest pengetahuan adalah 5,34±1,398 dan skor posstest 6.93±0,960, sedangkan skor pretest Sikap adalah 15,00±1,884 dan skor posttest 16,33±0,923. Pengaruh edukasi menggunakan metode E-Booklet VAKVID memberikan perbedaan yang signifikan terhadap pengetahuan (p=0,000) dan sikap (p=0,000) Pemahaman Vaksin Covid-19. Edukasi menggunakan metode e-Booklet VAKVID dapat meningkatkan pengetahuan dan sikap pemahaman vaksin Covid-19 pada siswa.